2011
DOI: 10.1001/archoto.2011.192
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant <emph type="ital">Staphylococcus aureus</emph> Colonization in Otitis-Prone Children

Abstract: The prevalence of MRSA colonization among otitis-prone children was similar to rates reported among the general pediatric community. Methicillin-resistant S aureus colonization at the time of bilateral myringotomy and tube insertion was not predictive of subsequent otorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Staphylococcus aureus is the major cause of nosocomial infections. The importance of Staphylococcus aureus as a causative pathogen of OM came from the developing antibioticsresistance of these bacteria and their high ability of colonization (15,16). This agrees with the result mentioned by (17) reported that S. aureus was the most prominent causative agent of CSOM in children older than six years.…”
Section: Discussionsupporting
confidence: 81%
“…Staphylococcus aureus is the major cause of nosocomial infections. The importance of Staphylococcus aureus as a causative pathogen of OM came from the developing antibioticsresistance of these bacteria and their high ability of colonization (15,16). This agrees with the result mentioned by (17) reported that S. aureus was the most prominent causative agent of CSOM in children older than six years.…”
Section: Discussionsupporting
confidence: 81%
“…Very rarely, intravenous antibiotics may be required for unrelenting tube otorrhea but in these cases, other underlying comorbidities such as immunological deficiencies and primary ciliary dyskinesia must be ruled out. 72,73 In addition, methicillin-resistant Staph aureus (MRSA) has been reported as a cause of prolonged tube otorrhea, 74 but one recent study did not demonstrate a significant difference between MRSA and non-MRSA otorrhea, in regards to the required management and sequelae. 75 It is important to note that many topical substances have been associated with ototoxicity and therefore careful diligence should be practiced when prescribing ear drops, especially in children with tympanostomy tubes.…”
Section: Tube Otorrheamentioning
confidence: 99%
“…Consequently, Methicillin-Resistant Staphylococcus Aureus (MRSA) infections cannot be treated with commercially available ciprofloxacin ototopical drops. 1 , 2 The prevalence of MRSA in chronic suppurative otitis media (CSOM) is known to be more than ∼60–70% among S. Aureus isolates from hospitals in Korea. 3 Besides CSOM, MRSA is an emerging problem related to chronic pediatric tympanostomy tube otorrhea.…”
Section: Introductionmentioning
confidence: 99%